Anti-Probiotic Effects of Essential Oils from Some Turkish Endemic Thyme Species - Cetin, Bulent; Cakmakci, Songul; Gurses, Mustafa (Asian Journal of Chemistry, 2013)
Antimicrobial effects of essential oils from endemic thyme species in Turkey were examined in vitro on some probiotic microorganisms. Three thyme species (Origanumacutidens, Origanumrotundifolium, Thymus sipyleus subsp. sipyleus var. rosulans) and six probiotic bacteria (Bifidobacterium bifidum, Lactobacillus acidophilus, Lactobacillus bulgaricus, Lactobacillus plantarum, Lactobacillus reuteri and Streptococcus thermophilus) were tested. The disc diffusion and microwell dilution assay methods were used to determine antimicrobial effects of the essential oils. Disc diffusion zone diameters and MIC values of the samples were found as 16-48 mm and 7.80-500 μg/mL, respectively. The carvacrol was detected as the main component by GC-MS analyses. Lactobacillus bulgaricus and Streptococcus thermophilus were the most sensitive strains to the essential oils. Lactobacillus acidophilus and Lactobacillus reuteri were more resistance than the other strains. It was concluded that the high level of thyme can negatively influence the intestinal microflora and particularly the quality of fermented foods.